2022
DOI: 10.1177/00169862221110875
|View full text |Cite
|
Sign up to set email alerts
|

The Two Sides of Cognitive Masking: A Three-Level Bayesian Meta-Analysis on Twice-Exceptionality

Abstract: We compared the Wechsler scores of individuals with twice-exceptionality (2e) and giftedness using a three-level Bayesian meta-analysis. Ninety-five effect sizes were calculated from 15 studies ( n = 2,106). Results show that individuals with 2e who have learning disabilities perform lower than individuals with giftedness in Full-Scale Intelligence Quotient (FSIQ; g = −0.62), working memory ( g = −0.79), and processing speed ( g = −0.75). Individuals with 2e who have attention-deficit/hyperactivity disorder ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 92 publications
(135 reference statements)
0
8
0
Order By: Relevance
“…Thus, a more apt conclusion to draw from the research of Toffalini et al might be that giftedness is over-represented amongst students who are assessed for an LD (as opposed to those who have an LD). Given the acknowledged under-diagnosis of 2e-LD students (a consequence of the masking of both strengths and weaknesses; Atmaca & Balo glu, 2022;Maddocks, 2020), it could be hypothesised that participants in Toffalini et al's sample were more likely to represent those with severe rather than moderate or mild dyslexia, that is, those whose discrepant profiles were more apparent to teachers and parents. Indeed, based on the inclusion criteria used in the Toffalini et al study, all students identified as G-LD had, at a minimum, a striking 4 SD discrepancy between their cognitive strength (a GAI of 130+) and their academic weakness (an achievement score of <70 in one specific area of achievement).…”
Section: Assessment Practices Used To Identify Gifted-dyslexic (G-d) ...mentioning
confidence: 99%
“…Thus, a more apt conclusion to draw from the research of Toffalini et al might be that giftedness is over-represented amongst students who are assessed for an LD (as opposed to those who have an LD). Given the acknowledged under-diagnosis of 2e-LD students (a consequence of the masking of both strengths and weaknesses; Atmaca & Balo glu, 2022;Maddocks, 2020), it could be hypothesised that participants in Toffalini et al's sample were more likely to represent those with severe rather than moderate or mild dyslexia, that is, those whose discrepant profiles were more apparent to teachers and parents. Indeed, based on the inclusion criteria used in the Toffalini et al study, all students identified as G-LD had, at a minimum, a striking 4 SD discrepancy between their cognitive strength (a GAI of 130+) and their academic weakness (an achievement score of <70 in one specific area of achievement).…”
Section: Assessment Practices Used To Identify Gifted-dyslexic (G-d) ...mentioning
confidence: 99%
“…These obstacles impact the type of services that twiceexceptional students receive and may prevent them from receiving the support they require (Amend, 2018). For instance, those identified with disabilities only may not develop their full potential in education, whereas those identified as gifted may not receive support for their disability (Atmaca and Baloğlu, 2022). This misalignment between student needs has several undesirable consequences.…”
Section: Defining Intellectual Giftedness and Twice-exceptionalitymentioning
confidence: 99%
“…In addition, cognitively gifted learners are assumed to be high achievers in all academic subjects. Rather, individual differences in intelligence profiles will show relative strengths and weaknesses in actual academic achievements (Atmaca & Balogu, 2022; Brody & Mills, 1997; Gelbar et al, 2022; Maddocks, 2020; McCallum et al, 2013; Webb et al, 2016).…”
Section: Definitionsmentioning
confidence: 99%